Molecular diversity in pathogenic variants of Vibrio parahaemolyticus in Peru [Diversidad molecular de variantes patogénicas de Vibrio parahaemolyticus en el Perú] - Caro-Castro J. (2020)
During the period from 1995 to 2017, in order to determine the diversity of Vibrio parahaemolyticus pathogenic variants in Peru, 102 Peruvian genomes (97 from a hospital setting and 5 from an out-of-hospital setting) were analyzed using the multilocus typification scheme and BLASTn in the search for virulence genes. Fifteen different sequence types were identified. It was found that the ST3 genotype, which is found in the pandemic clone, was the most abundant, with 52% (n=53); followed by ST120, with 23.5% (n=24); and the CC345 clonal complex, with 11.8% (n=12). A total of 89 analyzed strains presented genes encoding the pathogenicity island VpaI-7 (87.3%), while 96 presented the tdh gene (94.1%), and 6 the trh gene (5.9%). The ST3 genotype was the predominant one during the evaluated period, this genotype was the cause of a major outbreak in Peru’s past history. Other pathogenic genotypes found represent a latent public health risk associated with seafood consumption. © 2020, Instituto Nacional de Salud. All rights reserved.